BASIC EXERCISES WITH KETTLEBELL - Emir Altumbabić, (Sport Scientific And Practical Aspects, 2025)
This work is based on the presentation of basic exercises with kettlebells, such as dead lift, squat, swing, clean, press, snatch and get up. The paper presents 7 basic exercises that are used in training with kettlebells. With the help of images, clear positions of the body are displayed during each exercise, in order to explain as clearly as possible learning basic techniquaes, one part of the work is dedicated to breathing during exercise.